Intelligent Miniature Circuit Breaker - Benjamin Kommey; Seth Djanie Kotey; Eric Tutu Tchao; Gideon Adom Bamfi (Computer Engineering and Applications Journal, 2021)
The traditional electrical distribution panel (or breaker panel) is a system that divides the main electrical power feed and distributes them to subsidiary circuits whiles providing a protective mechanism via the use of miniature circuit breakers, residual current devices, etc. The conventional panel distributes electrical power alright but the system does not make provision for any form of real time monitoring and feedback of power consumption levels in the home. This paper presents a design of a miniature circuit breaker distribution panel integrated with other electronic devices which helps achieve real time monitoring of power consumption and also automatically trips the circuit if there is a fault and reconnects the circuit if the fault is cleared to ensure little to no interruption in electricity to appliances.